The role of figurative nominations in formation of the concept «Loneliness» in a mystery novel by Ray Bradbury «Death Is a Lonely Business» (Proceedings of Southern Federal University. Philology, 2015)
Shushmarchenko Ekaterina AleksandrovnaThe article describes the concept «Loneliness» in fiction built upon the descriptions from the mystery novel by Ray Bradbury «Death Is a Lonely Business» where the concept shows up in figurative nominations that concretize conceptual dimensions and reveal its mental aspects. The results of the research present the individual idea of the loneliness in the text of the novel.Key words: concept «Loneliness», figurative nominations, mental conceptual dimensions, concept in fiction.